Allium macrostemon Bunge. exerts analgesic activity by inhibiting NaV1.7 channel. (5th December 2021) - Yang, Xiaopei; Dai, Yuwen; Ji, Zhilin; Zhang, Xiangyi; Fu, Wei; Han, Chaochi; Xu, Yunsheng
Abstract: Ethnopharmacological relevance: Allium macrostemon Bunge. is an edible Chinese herb traditionally used for the treatment of thoracic pain, stenocardia, heart asthma and diarrhea. Although its biological potential has been extensively proven such as antioxidant activity, antiplatelet aggregation, vasodilation and antidepressant-like activity, there are no reports in the literature regarding its pharmacological analgesic activity. Aim of the study: The study was carried out to examine the anti-nociceptive activity of the crude extract of A. macrostemon bulbs and interpret its likely molecular target. Materials and methods: The bulbs of A. macrostemon were gathered, dried-up, and extracted with water (AMWD). AMWD was subjected to activity testing, using chemical-induced (acetic acid and formalin test) and heat-induced (hot plate) pain models. To evaluate the likely mechanistic strategy involved in the analgesic effect of AMWD, whole-cell patch clamp recordings were conducted in acutely dissociated dorsal root ganglion (DRG) neurons and human embryonic kidney 293T (HEK293T) cells expressing pain-related receptors. Electrophysiological methods were employed to detect the action potentials of DRG neurons and potential targets of A. macrostemon. Results: AMWD showed significant palliative effect in all heat and chemical induced pain assays. Moreover, AMWD significantly reduces the excitability of dorsal root ganglion neurons by reducing the firing frequency of action potentials. Further analysis revealed that voltage-gated sodium channel Nav1.7 is the potential target of A. macrostemon for its analgesic activity. Conclusion: This study has brought new scientific evidence of preclinical efficacy of A. macrostemon as an anti-nociceptive agent. Apparently, these effects are involved with the inhibition of the voltage-sensitive Nav1.7 channel contributing to the reduction of peripheral neuronal excitability. Our present study justifies the folkloric usage of A. macrostemon as a remedy for several pain states . Furthermore, A. macrostemon is a good resource for the development of analgesic drugs targeting Nav1.7 channel. Graphical abstract: Image 1